PERBEDAAN REAKSI PEMBERIAN TRANSFUSI DARAH WHOOLE BLOOD (WB) DAN PACKED RED CELL (PRC) PADA PASIEN SECTIO CAESARE - neila sulung (Universitas Fort De Kock, 2016)
Transfusion reaction is the reaction of the recipient's body to blood donors, blood transfusion reactions can be mild to severe, and could be either fast, medium and slow. Hospital Dr. Achmad Darwis District Lima Puluh Kota every month UTDRS blood for transfusion are 45 to 55 bags. Survey of 30 patients who received a blood transfusion, there are 10 people have reactions such as fever of 4 people, as many as 4 people dizzy, urtikariat (itching) as much as one person and as many as three people shivering. The aim of research to find out the difference Reaction Giving Whoole Blood Transfusion Blood (WB) and Packed Red Cell (PRC) in Patients Sectio Caesare (SC). Type pre-experimental study, the design of Static Group Comparison. The population was patients post SC who receive blood transfusion, with sampling purposive sampling of 20 people. The data collection was done by direct observation, then processed and analyzed using independent t-test. Results that the average transfusion reactions in patients receiving blood transfusions WB is 1.30 and the patients who receive blood transfusion PRC is 0.40. The results of the bivariate no difference Whoole blood transfusion reaction Blood (WB) and Packed Red Cell (PRC) in Patients with Post Sectio Caesarea (SC) (p = 0.009). It was concluded that there is a difference of transfusion reactions in blood transfusions WB and blood transfusions PRC. Expected to medicine and nurse to be more selective in giving blood transfusions to patients and intensive control of blood transfusion process , so that a transfusion reaction can be immediately known. . Keywords: transfusion reactions, Whoole Blood (WB), Packed Red Cell (PRC) Reaksi Transfusi adalah reaksi tubuh resipien terhadap darah donor, reaksi transfusi darah dapat ringan sampai berat, dan dapat berupa reaksi cepat, sedang, dan lambat. RSUD Dr. Achmad Darwis Kabupaten Lima Puluh Kota setiap bulannya UTDRS mengeluarkan darah untuk transfusi berjumlah 45 sampai 55 kantong. Survey terhadap 30 orang pasien yang mendapatkan transfusi darah, terdapat 10 orang mengalami reaksi berupa demam sebanyak 4 orang, pusing sebanyak 4 orang, menggigil sebanyak 3 orang dan urtikariat (gatal-gatal) sebanyak 1 orang. Tujuan penelitian untuk mengetahui Perbedaan Reaksi Pemberian Transfusi Darah Whoole Blood (WB) dan Packed Red Cell (PRC) pada Pasien Sectio Caesare (SC). Jenis penelitian pra eksperimen, dengan rancangan Statis Group Comparison. Populasi adalah pasien post SC yang mendapatkan transfusi darah, dengan pengambilan sampel secara purposive sampling sebanyak 20 orang. Pengumpulan data dilakukan dengan cara observasi langsung, kemudian diolah dan dianalisa menggunakan t-test independent. Didapatkan hasil rata- rata reaksi transfusi pada pasien yang mendapatkan transfusi darah WB adalah 1,30 dan pasien yang mendapatkan transfusi darah PRC adalah 0,40. Terdapat perbedaan reaksi pemberian transfusi darah Whoole Blood (WB) dan Packed Red Cell (PRC) pada Pasien Post Sectio Caesarea (SC) (p = 0,009). Disimpulkan bahwa ada perbedaan reaksi transfusi pada transfusi darah WB dan transfusi darah PRC. Diharapkan dokter dan perawat agar lebih selektif dalam memberikan darah transfusi pada pasien dan intensif dalam mengontrol proses transfusi darah, sehingga adanya reaksi transfusi dapat segera diketahui. Kata Kunci : Reaksi Transfusi, Whoole Blood (WB), Packed Red Cell (PRC)